Serious haematological toxicity during and after ipilimumab treatment: a case series - Simeone, Ester (BioMed Central, 2014)
INTRODUCTION: Immunotherapy with the anti-cytotoxic T-lymphocyte antigen-4 monoclonal antibody ipilimumab has been shown to improve overall survival in previously treated and treatment-naïve patients with unresectable stage III or IV melanoma. Consistent with its proposed immunomodulating mechanism of action, the most common toxicities associated with ipilimumab therapy are immune-related in nature and include those related to the skin and gastrointestinal tract, with endocrine and hepatic events also frequent. Other rare adverse events, including haematological aberrations, may also occur and can have serious consequences if unrecognised. Here we describe three patients who developed serious haematological adverse events during or after treatment with ipilimumab. CASE PRESENTATION: Three Caucasian patients (two women aged 68 and 49 years and one man aged 70 years) with metastatic melanoma experienced anaemia and/or leukopenia (neutropenia) with toxicity of various grades during or after treatment with ipilimumab, without significant changes to other haematological values. Two of the patients stopped treatment after the third ipilimumab dose, one because of severe anaemia that required blood transfusion and the other due to febrile neutropenia that was treated with antibiotics and granulocyte-macrophage colony-stimulating factor stimulation. The third patient developed anaemia and leukopenia after treatment during the follow-up period. The results of autoimmunity tests performed were positive and corticosteroids were used to treat these events as per side-effects treatment algorithms specifically developed for the management of immune-related adverse events associated with ipilimumab, an approach that was safe and effective. CONCLUSIONS: Haematological toxicity is a rare but potentially serious immune-related side effect of ipilimumab therapy. However, if promptly recognised and treated, haematological toxicity is manageable and can be reversed with standard corticosteroid treatment as recommended for other ipilimumab immune-related side effects.